A REVIEW ON HUMAN ERROR IN MALAYSIA MANUFACTURING INDUSTRIES - Jian Ai Yeow; Poh Kiat Ng; Hen Toong Tai; Mei Min Chow, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
Human error is a serious concern in manufacturing industries. It affects product error and liability and even leads to workplace injuries or fatalities. Malaysia has recorded a worrying figure of workplace accidents and injuries. In 2018 alone, there were more than 2700 workplace accidents which led to disabilities and death. A workplace accident would result in a no-win situation for a company. Manufacturing sectors in Malaysia make the highest claims from the total cost of accidents and injuries. The Department of Occupational Safety and Health (DOSH) in Malaysia also imposes a fine for companies who breach safety and health regulations in the workplace. Inspections are carried out to ensure that manufacturers obey the rules of occupational safety and health (OSH), and fined for being errant employers. However, these penalisations are often due to the negligence and lack of awareness among employers and employees. Hence, it is of interest for researchers to identify the root causes of human error among manufacturing industries in Malaysia. This review highlights the common causes of workplace accidents and injuries in manufacturing through observation. Several well-known human error models since 1983 are also investigated. The potential outcome of this review is to improve OSH awareness among manufacturers for a more sustainable future in their business, employment, and social well-being